Extraction of niobium and tantalum from ferrocolumbite by hydrofluoric acid pressure leaching - Rodriguez, Mario Humberto (2015)
Abstract Pressure acid leaching was used to extract niobium and tantalum from a ferrocolumbite ore. The leaching was carried out in a pressure reactor using hydrofluoric acid as leachant. Various parameters, such as temperature, reaction time, HF concentration, stirring speed, particle size and solid-to-liquid ratio in the leaching process, were optimized. The reactants and products were characterized by X-ray fluorescence (XRF), X-ray diffraction (XRD) and specific surface area (BET). Experimental results showed that the maximum extraction of Nb and Ta, 90 and 80% respectively, it was achieved at an HF concentration of 9% v/v, reaction temperature of 220°C, particle size of - 45 μm, solid-to-liquid ratio of 1.82% w/v and reaction time of 80 min. Crystalline structures, different from those originally present in the ore, were not detected by XRD analysis of the leaching residues.